Strategi pemilihan komunikator dalam diseminasi informasi kesehatan melalui program “Waktu Belajar II” di TPST Bantar Gebang Bekasi - Monica Amalya Pratiwi; Neneng Komariah; Rully Khairul Anwar (Faculty of Communication, Padjadjaran University, 2021)
In the process of dissemination information that mostly designed and carried out in an organized manner, the role of communicator is very impactfull to the successness of information delivery and also to gaining the trust or good responses from the audience. In order to get a good communicator, creating a strategy for selecting communicator is one of the good way that can be done and an important aspect that must be considered. This research aims to determine how the process of selecting a communicator strategy that carried out by GPSTEPS went using the theory of communicator requirements according to Cangara (credibility, attractiveness, and strength) and knowing the details of the stages of the strategy. The focus of this research consists of four stages of the GPSTEPS’s communicator selection strategy which are the selection of division heads, open volunteer recruitment, screening material regarding the GPSTEPS profile and health information to be submitted according to each division, and conduct special training to support the skills and creativity of communicators. This research was also conducted to provide a new perspective in determining the qualifications of a good communicator. The research method used is descriptive research with a qualitative approach. Data collection techniques are using observation, interviews, and documentation study. The results showed that from stages of strategy for selecting communicators for the Waktu Belajar II program, GPSTEPS got the main communicator (each division heads) who has been determined using the GPSTEPS’s rotating system and the communicator’s assistant (volunteers) who has been determined by each division heads according to their performance, commitment, and credibility during the selection stage. The communicator selection strategy for Waktu Belajar II program was made by GPSTEPS to meet the qualifications of a good communicator for the Bantar Gebang Bekasi’s integrated landfill children.